Studies on the extra-mitochondrial CoA-ester formation of valproic and Delta(4)-valproic acids - Aires, Catia C. P. (2015)
The hypothesis whether valproic acid (VPA) and its main microsomal metabolite, Delta(4) -valproic acid, can be activated to the respective CoA esters in the cell cytosol was investigated. The valproyl-CoA formation was measured in different subcellular fr